A rare case of congenital anterior urethral diverticulum in a two-year-old boy - Stoyan Peev; Teofil Pelov; Emil Dorosiev; Boris Mladenov; Bojana Stoeva; Boyan Stoykov (Urology Case Reports, 2021)
Congenital diverticulum is a very rare disease of the urethra in which there is a sacculus enlargement on its ventral surface. We present a Case of a 2-year-old boy with symptoms of urinary hesitancy and swelling in the penoscrotal angle that appears during micturition. The diagnosis of urethral diverticulum is confirmed by retrograde urethrography and voiding cystogram. An open operation was performed - diverticulectomy and primary repair of the urethra.